Pimenta pseudocaryophyllus (Gomes) L. R. Landrum (Myrtaceae): stem and leaf anatomy of a medicinal plant - Custódio, Dayana Lacerda; Kolb, Rosana Marta [UNESP]; Faria, Terezinha de Jesus; Bianchini, Edmilson (Universidade Estadual de Londrina, 2013)
The study of medicinal plants involves several areas of science. Anatomy contributes to species identification and consequently, with quality control of plant product. This paper describes the leaf and stem anatomy of Pimenta pseudocaryophyllus (Gomes) L.R. Landrum (Myrtaceae), collected in Seasonal Semideciduous Forest. The studied organs presented uniseriate epidermis covered by a thick cuticle and secretory cavities. The stem showed a continuous ring of vascular tissues around the pith, with phloem on both sides of the xylem. The leaf was hypostomatic, with trichomes on the abaxial face, with bifacial mesophyll and amphicrival vascular bundle, surrounded by a sclerenchymatous pericycle in the petiole and in the midrib. Among the histochemical tests, positive results were obtained for lipids, phenolic compounds, starch and calcium oxalate (druses). The species had anatomical features typical of the family and the secretory cavities present in leaves and stems were related to the secondary metabolites detected.

O estudo de plantas medicinais envolve várias áreas da ciência. Neste contexto, a anatomia contribui para a identificação da espécie e consequentemente, com a qualidade do produto da planta. Este trabalho descreve a anatomia do caule e da folha de Pimenta pseudocaryophyllus (Gomes) L.R. Landrum (Myrtaceae), coletada em Floresta Estacional Semidecidual. Os órgãos estudados apresentaram epiderme unisseriada, recoberta com cutícula espessa, e cavidades secretoras. O caule apresentou anel contínuo de tecido vascular ao redor da medula, com o floema em ambos os lados do xilema. A folha foi hipoestomática com tricomas na face abaxial, com mesofilo bifacial e feixe vascular anficrival circundado por periciclo esclerenquimático no pecíolo e na nervura principal. Entre os testes histoquímicos, resultados positivos foram obtidos para lipídeos, compostos fenólicos, amido e oxalato de cálcio (drusas). A espécie apresentou aspectos anatômicos típicos da família e as cavidades secretoras presentes nas folhas foram relacionadas aos compostos secundários detectados
Pimenta pseudocaryophyllus (Gomes) L. R. Landrum (Myrtaceae): anatomia do caule e da folha de uma planta medicinal
Keywords: Secondary metabolites; Secretion; Secretory cavities; Tropical tree; Cavidades secretoras; Compostos secundários; Espécies tropicais; Secreção